Fallbegleitende DRG-Kodierung: Verbesserung von Wirtschaftlichkeit und Dokumentationsqualität in der stationären Versorgung - Geuß, Steffen; Baumgart, André (Der Chirurg, 2018)
Background: In prospective reimbursement schemes a diagnosis-related group (DRG) is assigned to each case according to all coded diagnoses and procedures. This process can be conducted retrospectively after (DC) or prospectively during the hospitalization (PC). The use of PC offers advantages in terms of cost-effectiveness and documentation quality without impairing patient safety. Material and methods: A retrospective analysis including all DRG records and billing data from 2012 to 2015 of a surgical department was carried out. The use of PC was introduced into the vascular surgery unit (VS) in September 2013, while the remaining surgical units (RS) stayed with DC. Analysis focused on differences between VS and RS before and after introduction of PC. Characteristics of cost-effectiveness were earnings (EBIT-DA), length of stay (LOS), the case mix index (CMI) and the productivity in relation to the DRG benchmark (productivity index, PI). The number of recorded diagnoses/procedures (ND/NP) was an indicator for documentation quality. Results: A total of 1703 cases with VS and 27,679 cases with RS were analyzed. After introduction of PC the EBIT-DA per case increased in VS but not in RS (+3342 Swiss francs vs. +84, respectively, p < 0.001). The CMI increased slightly in both groups (+0.10 VS vs. +0.08 RS, p > 0.05) and the LOS was more reduced in VS than in RS (−0.36 days vs. −0.03 days, p > 0.005). The PI increased in VS but decreased in RS (+0.131 vs. −0.032, p < 0.001), ND increased more in VS (+1.29 VS vs. +0.26 RS, p < 0.001) and NP remained stable in both groups. Conclusion: The use of PC helps to significantly improve cost-effectiveness and documentation quality of in-patient hospital care, essentially by optimizing LOS and cost weight in relation to the DRG benchmark, i. e. increasing the PI. The increasing ND indicates an improvement in documentation quality.
First Online: 29 November 2017
Gesehen am 01.04.2019